Vacuole Disruption as the Primary Fungicidal Mechanism of Action of Polygodial, a Sesquiterpene Dialdehyde - Kondo, Takuya; Takaochi, Yusuke; Yamaguchi, Yoshihiro; Ogita, Akira; Fujita, Ken-ichi; Tanaka, Toshio (Planta Medica International Open, 2016)
The fungicidal mechanism of action of polygodial was examined in malt extract medium in which lethality against Saccharomyces cerevisiae was achieved at a much lower dose than in glucose-containing nutrient medium. Vacuolar membrane disruption, rather than cellular oxidative stress induction and damage to the plasma membrane, was considered the most likely lethal event underlying these observations. Vacuolar membrane disruption and polygodial-mediated lethality were similarly observed against the pathogenic fungi Candida albicans and Aspergillus niger.
Keywords: polygodial; fungicidal activity; vacuole; Saccharomyces cerevisiae